Proceedings, high altitude revegetation workshop no. 6 - Colbert, Thomas A., editor; Cuany, Robin L., editor; Colorado State University, Water Resources Research Institute, publisher (Colorado State University. Libraries, 1984)
The 6th high altitude revegetation workshop was held on March 5-6, 1984 at Colorado State University in Fort Collins, Colorado.
Keywords: Revegetation -- United States -- Congresses; Mountain plants -- United States -- Congresses; Tundra plants -- United States -- Congresses; Reclamation of land -- United States -- Congresses